Profile of Sofosbuvir and Velpatasvir Combination in the Treatment of Chronic Hepatitis C in Children and Adolescents: Current Evidence - Brigham D; Narkewicz MR (Dove Medical Press, 2024)
Dania Brigham, Michael R Narkewicz Digestive Health Institute, Pediatric Liver Center, Children's Hospital Colorado and University of Colorado School of Medicine, Section of Pediatric Gastroenterology, Hepatology and Nutrition, Aurora, CO, USACorrespondence: Michael R Narkewicz, Email michael.narkewicz@childrenscolorado.orgAbstract: Chronic hepatitis C (HCV) affects up to 3.25 million children and adolescents. Early treatment of HCV in children and adolescents reduces progression to advanced liver disease and cancer. Treatment for HCV has evolved to highly effective direct acting antiviral therapy in adults and now in children ≥ 3 years of age. This review focuses on the role of sofosbuvir and velpatasvir (SOF/VEL), a newer treatment of children and adolescents with chronic HCV. SOF/VEL is a pangenotypic DAA with primary clearance via the liver and biliary excretion. It has been studied in children and adolescents and is approved in the US for use in children and adolescents ≥ 3 years of age. Although the data are currently limited, SOF/VEL has demonstrated sustained viral response rates similar to comparable DAAs in the range of 95- 98%. To date, side effects have been minimal.Keywords: pediatric hepatitis C, pediatric hepatitis C treatment